The Relationship Between Risky Food Consumption Behavior And The Incidence Of Obesity In The Community Tanjung Anom: Food Consumption Behavior - Jantrisa Maria Magdalena; Derang, Imelda; Ginting, Friska (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Obesity is an increase in fat accumulation that results in weight gain and disturbs health, this is caused by a lack of physical activity carried out and poor or unhealthy dietary arrangements such as foods that contain high fat, sweet, salty, irregular eating frequency. This study aims to determine the relationship between risky food consumption behavior and the incidence of obesity in the Tanjung Anom community in 2023. Methods: The research was observational analytic with a cross sectional design. The study population was 10,087, of which the sample was taken as many as 92 people. Sampling was taken by simple random sampling technique. Data were taken directly using questionnaires and measuring instruments meters and scales. Results: The results of the study found that risky food consumption behavior was not good at 63.0% and obestias at 80.0%. Based on the results of the chi square test, it was found that the p value = 0.001 (<α=0.05) Conclusions: meaning that there is a relationship between risky food consumption behavior and the incidence of obesity. It is hoped that the Tanjung Anom community will always pay attention to health by regulating diet and increasing simple physical activity during free time to reduce the occurrence of obesity and the impact of obesity in the local community.